Nutraceutical Potential of Seaweed Polysaccharides: Structure, Bioactivity, Safety, and Toxicity. Issue 3 (1st April 2019) - Tanna, Bhakti; Mishra, Avinash
Abstract: In recent years, marine organisms including seaweeds have been highlighted as potential sources of useful metabolites and bioactive compounds, with vast biological and physiological activities. Seaweeds have long been used as a food source, for medicinal purposes, and as dietary supplements in various Asian countries, and their potential benefits have recently attracted the attention of many Western and European countries. Their commercial value depends on their applications in the food, nutraceutical, and pharmaceutical industries. Seaweeds are considered a potential source of nutraceuticals or functional foods, and analysis of taste‐oriented motives has revealed that seaweeds are preferentially selected over other types of marine foods by seafood consumers and people with high levels of health, education, and living status. It is a general perception that health conscious people prefer environmentally friendly food sources, and present an opportunity to focus on seaweed‐based foods, which have significant nutritional benefits to humans. Among the various bioactive constituents, seaweed polysaccharides have been proven to possess various beneficial properties including anticoagulant, anti‐inflammatory, antioxidant, anticarcinogenic, and antiviral activities. The diversity and composition of seaweed polysaccharides play vital roles in these biological activities. Seaweeds are a rich source of sulfated polysaccharides, which are responsible for much of the bioactivity, as they can interact with various textures and cellular proteins. A number of toxicological assays and clinical trials suggest that the ingestion of seaweeds as functional foods should be considered worldwide to improve immune responses. In this review, different polysaccharides from seaweeds and their compositions and potential nutraceutical applications are discussed.